The Modern Indonesian Experience in Coexistence between Muslims and Others: Presentation and Evaluation - Zaim, Muntaha Artalim (Al-Daulah : Journal of Criminal Law and State Administration Law, 2024)
Research Objective: This study investigates the experience of religious coexistence in Indonesia, specifically focusing on the interactions between Muslims and followers of other religions. It analyzes the conceptual frameworks and socio-political developments that shape this coexistence. The goal is to evaluate how Islamic principles intersect with pluralistic values and how these dynamics have evolved within the Indonesian context. Research Method: The research employed a qualitative-descriptive approach through comprehensive library research. It integrated classical Islamic sources with modern academic discourse to construct a comparative and historical analysis: religious texts and legal documents were the foundation for this investigation. Results: The findings indicate that state policies, such as Pancasila, historical accommodations, and socio-cultural integration, have influenced religious coexistence in Indonesia. Additionally, the research demonstrates that Islamic teachings support coexistence within specific theological and legal frameworks, without endorsing religious relativism. Findings and Implications: The Indonesian model of coexistence has evolved from doctrinal rigidity to practical tolerance. This research highlights that pluralism in Indonesia functions more as a sociopolitical construct than a convergence of theologies. These insights challenge liberal interpretations of religious harmony and provide a more transparent framework for understanding interfaith coexistence in Muslim-majority societies. Conclusion: Religious coexistence in Indonesia represents a complex interplay of Islamic theology, state ideology, and socio-cultural adaptation. Promoting harmony while maintaining doctrinal integrity requires a nuanced understanding of Islamic jurisprudence and national philosophy. Contribution: This study contributes to the academic discourse on Islam and pluralism by offering a structured framework for evaluating religious coexistence to bridge classical Islamic epistemology with contemporary realities, particularly in Southeast Asia. Limitations and Suggestions: The research is limited by its focus on Indonesia and classical Islamic sources. Future studies should incorporate fieldwork, broader comparative perspectives, and empirical data to validate and expand upon these findings.